Guiding the Practice: Design thinking to meet the needs of FNMI students in Saskatchewan - Jeremy Murphy (ETAD Summer Institute, 2024)
Peer Reviewed Throughout the last 30 years, a concerted effort has been to undo the legacy of First Nations Education in Canada. With this, there has been an increase in the exploration of how to teach effectively and design courses for a FNMI (First Nations, Metis, Inuit) audience. What are the considerations that we should take when designing a course? What specifics must we consider in developing courses for FNMI learners in a school setting? How do we ensure that we meet our learners where they are instead of forcing them to exist in a paradigm that does not work for them? Throughout this process, I have discovered that though we talk quite a bit about this topic, there are many areas that we lack understanding of or a desire to take into account regarding the actual variables that exist within the teaching of FNMI students. This process and these proceedings will act as a starting point for us to develop a guide for many teachers that directly synthesizes the information available within the realm of teaching and learning.